Management of digitisation of educational institutions − improvement model - Jolanta Religa; Anna Wronka (Institute of Social Affairs of the Pedagogical University of Cracow, 2023)
The COVID-19 pandemic has disrupted the education process, including the education and vocational training sector, where readiness to switch to remote learning was not common and obvious. In this exceptional situation, the need to digitise both didactic and organizational processes in institutions of continuing education and vocational training, and the need to ensure the quality of these processes has become even more evident. While skilful management with the support of diff erent tools, including improvement models, is a chance for educational units to survive in a turbulent environment and even to build a lasting competitive advantage. The article presents a proposal to support educational institutions in digitisation processes, developed as part of the international project Quality for digital education readiness in VET (Q4EDU), implemented in 2021-2023 by a partnership of seven institutions from four European Union countries (Polish, Greece, Cyprus and Italy). The proposed methodology is a comprehensive and universal solution for assessing the readiness of education and training institutions for the so-called deep digitisation, including pedagogical, technological and organizational aspects of their functioning. It offers the opportunity to monitor and improve the level of digitalisation through the use of an IT tool, based on the European framework DigCompOrg, and the opportunity to acquire and validate the competence of a digital education expert. The pilot phase in four partner countries has yielded promising results as expressed in the feedback of DigiRAsT users. The tool is available free of charge to staff interested in the development of the institution. Zarzadzanie cyfryzacją instytucji edukacyjnych - model doskonalący Pandemia COVID-19 zakłóciła proces edukacji, w tym sektor kształcenia i szkolenia zawodowego, w którym gotowość do przejścia na kształcenie zdalne nie była powszechna i wystarczająca. W tej wyjątkowej sytuacji jeszcze bardziej widoczna stała się potrzeba cyfryzacji, zarówno procesów dydaktycznych, jak i organizacyjnych w placówkach kształcenia ustawicznego i zawodowego oraz konieczność zapewnienia jakości tych procesów. Umiejętne zarządzanie przy wsparciu różnych narzędzi, w tym modeli rozwoju, jest szansą dla jednostek edukacyjnych na przetrwanie w turbulentnym otoczeniu, a nawet na zbudowanie trwałej przewagi konkurencyjnej. W artykule przedstawiono propozycję wsparcia instytucji edukacyjnych w procesach cyfryzacji, opracowaną w ramach międzynarodowego projektu Quality for digital education readiness in VET (Q4EDU), realizowanego w latach 2021-2023 przez partnerstwo siedmiu instytucji z czterech krajów Unii Europejskiej: Polski, Grecji, Cypru i Włoch. Proponowana metodyka jest kompleksowym i uniwersalnym rozwiązaniem pozwalającym na ocenę gotowości instytucji edukacyjnych i szkoleniowych do tzw. 86 Jolanta RELIGA, Anna WRONKA głębokiej cyfryzacji, obejmującej aspekty pedagogiczne, technologiczne i organizacyjne ich funkcjonowania. Oferuje możliwość monitorowania i doskonalenia poziomu digitalizacji poprzez wykorzystanie narzędzia informatycznego opartego na europejskich ramach DigCompOrg oraz możliwość nabycia i potwierdzenia kompetencji eksperta edukacji cyfrowej. Faza pilotażowych testów w czterech krajach partnerskich dała obiecujące wyniki wyrażone w opiniach użytkowników narzędzia DigiRAsT. Narzędzie jest dostępne bezpłatnie dla kadry zainteresowanych rozwojem instytucji.